Metabolism of diamantane by rat liver microsomal cytochromes P-450 - Hodek, P; Janscák, P; Anzenbacher, P; Burkhard, J; Janků, J; Vodicka, L (Xenobiotica; the fate of foreign compounds in biological systems, 1988)
1. Diamantane binds to liver microsomes from phenobarbital-treated rats with an apparent Ks value of 5.2 x 10(-7) mol/l. This value being lower than that obtained for perhydrophenanthrene indicates that diamantane is very strongly bound to microsomal cytochrome P-450. 2. Metabolic studies show that liver microsomes from phenobarbital-treated rats readily metabolize diamantane to mono-, di- and possibly tri-hydroxy derivatives, whereas liver microsomes from beta-naphthoflavone-induced rats do not bind this hydrocarbon or metabolize it. 3. Reconstituted cytochromes P-450 b and e were more efficient in the hydroxylation of diamantane than liver microsomes; metabolites formed by the reconstituted system do not include all the products formed by microsomes, which indicates the involvement of forms of cytochrome P-450 other than the isozymes b and e.
Keywords: jaterní mikrozomy; Microsomes, Liver; adamantan; Rats, Inbred Strains; krysa rodu Rattus; zvířata; Adamantane; Cytochrome P-450 Enzyme System; Chromatography, Gas; Male; Aminopyrine; Phenobarbital; Rats; Animals; mužské pohlaví; chromatografie plynová; fenobarbital; systém (enzymů) cytochromů P-450; aminopyrin; inbrední kmeny potkanů